2012
DOI: 10.1186/1756-3305-5-102
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an imidacloprid/flumethrin collar against fleas, ticks, mites and lice on dogs

Abstract: BackgroundThe studies reported here were conducted to ascertain the efficacy of imidacloprid/flumethrin incorporated in a slow-release matrix collar, against infestations of dogs by fleas, ticks, mites and lice. Efficacy was evaluated against the flea Ctenocephalides felis felis, the ticks Rhipicephalus sanguineus, Ixodes ricinus, Ixodes scapularis, Dermacentor reticulatus and Dermacentor variabilis, the mite Sarcoptes scabiei and the biting louse Trichodectes canis.MethodsGroups of collar-treated dogs (n = 7–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 27 publications
(41 reference statements)
3
46
1
Order By: Relevance
“…These findings correspond well to that recorded against Tunga penetrans following treatment with an imidacloprid / permethrin combination (Klimpel et al 2005). The rapid and sustained efficacy of a slow-release matrix collar formulation of 10 % (m/m) imidacloprid and 4.5 % (m/m) flumethrin (Seresto ® ) against laboratory infections of dogs with the cat flea C. felis has recently been demonstrated by Stanneck et al (2012). In addition, the efficacy of these collars in preventing infection with the cestode D. caninum in cats repeatedly infested with fleas infected with the metacestodes of the tapeworm has also been reported .…”
Section: Introductionsupporting
confidence: 66%
“…These findings correspond well to that recorded against Tunga penetrans following treatment with an imidacloprid / permethrin combination (Klimpel et al 2005). The rapid and sustained efficacy of a slow-release matrix collar formulation of 10 % (m/m) imidacloprid and 4.5 % (m/m) flumethrin (Seresto ® ) against laboratory infections of dogs with the cat flea C. felis has recently been demonstrated by Stanneck et al (2012). In addition, the efficacy of these collars in preventing infection with the cestode D. caninum in cats repeatedly infested with fleas infected with the metacestodes of the tapeworm has also been reported .…”
Section: Introductionsupporting
confidence: 66%
“…An evaluation of efficacy against I. holocyclus on IVP-treated dogs following shampooing or swimming was beyond the scope of this current study, but has been previously assessed for other tick species. Stanneck et al (2012b) found that the efficacy of the IVP in dogs that were shampooed or immersed in water every 28 days remained above 97 % and 94 %, respectively, against R. sanguineus and above 90 % and 89 %, respectively, against D. variabilis, over a period of 8 months. These results suggest that the active acaricidal compound remains in or on the hair and skin, or are replenished from the collar and thus support an assumption that regular shampooing or swimming should not markedly reduce the IVP's acaricidal efficacy against I. holocyclus.…”
Section: Discussionmentioning
confidence: 99%
“…This design gives us a clearer understanding of the acaricidal efficacy of the test product even under maximally unfavourable conditions (a tick attaching immediately to the spot of its first animal contact), whilst it disregards the repellent properties of pyrethroids that have been demonstrated for ticks in both in vitro (e.g. moving object bioassay) (Dautel and Cranna 2006) and in vivo studies (Horak et al 2012, Stanneck et al 2012b. As the adult, female I. holocyclus feed, they inject toxins into their host that can cause fatal paralysis in dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…External usecollar/ear tag Collars treated with imidacloprid/flumethrin offered accaricidal efficacy and repellent efficacy of 1 28 days after application (Stanneck et al, 2012a) Collars treated with imidacloprid/flumethrin offered accaricidal efficacy of 1 238 days after application Flumethrin External usecollar/ear tag Collars treated with imidacloprid/flumethrin offered accaricidal efficacy and repellent…”
Section: Studies Targeting Tick Species In Cats (Felis Catus)mentioning
confidence: 99%